PENEGAKAN HUKUM TERHADAP PUNGUTAN LIAR YANG DILAKUKAN OLEH PEGAWAI NEGERI SIPIL DINAS KEHUTANAN PROVINSI RIAU OLEH TIM SAPU BERSIH PUNGUTAN LIAR POLISI DAERAH RIAU - Malynda '; Erdianto Effendi; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
One form of corruption that often happens in everyday life is illegal levies.This also occurs in the realm of the Forestry Service, Civil Service Official of theForestry Service which in this case performs illegal levies is a member of forestpolice officers where forestry police are supposed to carry out their positions inaccordance with the power of law but instead perform actions that harm thepublic by abusing their power. In Indonesia, illegal levies are one of the forms ofcorruption crimes set out in Article 12 of Law Number 20 Year 2001 concerningthe Eradication of Criminal Acts of Corruption of Amendment of Law Number 31Year 1999 on Corruption, the article regulating the threat of sanctions that can beimposed against perpetrators of illegal punishment. But of course the regulationon sanctions alone is not enough to eradicate illegal pungli. Therefore, in order tofurther enforce the law related to illegal levies, the Government issuedPresidential Regulation No. 87 of 2016 on the Task Unit of Clean Sweep of IllegalDrawing. However, the dilemma itself for the team clean sweep illegal Polda Riauwhere efforts to enforce the law against illegal perpetrators because it does notexplain the nominal amount of levies that can be snared into Article 12 letter eLaw Number 20 Year 2001 on Corruption Eradication Corruption Act - LawNumber 31 Year 1999 on Corruption. The purpose of writing this thesis, namely;First, To know law enforcement against Civil Service Officer of Forestry Serviceof Riau Province who do illegal levies. Second, To know the legal issues thatoccur in law enforcement against Civil Service Officer Riau Forestry Servicewhich do illegal levies.From the results of research problems there are two main things that canbe concluded. Firstly, law enforcement by the Clean Sweep Team of Riau DistrictPolice Charges on Civil Service Officials of Riau Province Forestry Service whoimpose illegal levies is influenced by law enforcement factors. Secondly, the legalissue that occurs in the process of law enforcement against illegal levies by CivilService Officers of Riau Province Forestry Service is the complexity of problemsexperienced by law enforcers themselves where there is no reference to thenumber of illegal levies that can be categorized as illegal fees. This makes adilemma if there are illegal fees that have been considered to have a smallnominal, but if the transaction is often done then the nominal amount to be largeas well.Keywords : criminal act - illegal levies - law enforcement.